Actualism doesn’t have control issues : a reply to Cohen and Timmerman - Forcehimes, Andrew T. (2019)
Recently, Cohen and Timmerman (Journal of Ethics & Social Philosophy, 10(3), 1–18, 2016) argue that actualism has control issues. The view should be rejected, they claim, as it recognizes a morally irrelevant distinction between counterfactuals over which agents exercise the same kind of control. Here we reply on behalf of actualism.